A stochastic frontier model for measuring online bank profit efficiency - M. A. Baten; A. A. Kamil (South African Journal of Business Management, 2011)
This study revisited an alternative profit efficiency function specified by Berger Mester, (1997) and we applied Battese Coelli, (1995) inefficiency model as a unified and consistent framework in exploring the determinants of important factors causing profit efficiency differential on banking industry in Bangladesh. Using stochastic frontier technique we estimated bank specific profit efficiency for the period 2000 to 2007. This study attempted to examine the changes in the profit efficiency in accordance with NBs (Nationalized Commercial Banks), ISBs (Islamic Banks), FBs (Foreign Banks) and PBs (Private Banks) and significant variations of efficiencies across different kinds of banks in time periods. We found that the profit inefficiency has declined over the reference period and Translog Production Function is more preferable than Cobb-Douglas Production Function. Our results showed that Nationalized Commercial Banks were significantly inefficient and on the contrary ISBs, FBs, and PBs were efficient in producing profit and noteworthy. The estimated year wise average efficiencies of the sample banks from the profit efficiency model was 0.664 while group wise average profit efficiency was 0,639. Dhaka Bank is highly efficient with score 0.89 and AB Bank was found lowest efficient with score 0,35 according to the sample data.
Keywords: 650